How Science Takes Stock : The Story of Meta-Analysis - Hunt, Morton M., 1920-2016 (Book collections on Project MUSE., 1997)
He demonstrates how the statistical techniques of meta-analysis produce more accurate data than a standard literature review or the old-fashioned process of tallying up the results of each scientific study as if they were votes in an election. Further, Hunt answers skeptics who claim that dissimilarities between studies are often too significant for meta-analysis to be any more than an "apples and oranges" approach.